Optimizing Fertility Potential: A Review of Transition Cow Nutrition - Raja, Sengodan; Satheshkumar, Soundarapandian; Selvaraju, Mani; Prabaharan, Vaiyapuri; Ramachandran, Masilamani; Athinarayanan, Paramasivam (The Indian Journal of Animal Reproduction, 2025)
The period of transition in dairy cows occurs for a duration of three weeks before and after calving which affects the  reproductive efficiency and metabolic adaptation of the whole herd. Transition period is a phase during which the cows  are under stress physiologically owing to an increase in the nutrient demand which often results in negative energy bal ance (NEB), metabolic disorders, and fertility issues. Nutritional management such as feeding high energy diets includ ing bypass fat and dietary cation-anion difference (DCAD) are essential to alleviate NEB and sustain ovarian activity.  Monitoring biochemical profiles helps in formulating feeding regimes for imbalanced calcium, phosphorus, and Non esterified fatty acid (NEFA) levels. Custom nutritional strategies during the transition period aid in the optimization of  reproductive performance and reduce postpartum complications like hypocalcemia and ketosis. Implementing specific  nutritional strategies catered towards the need of the dairy herd can improve cow welfare and ensures sustainable dairy  production. The formulation of diets along with tailored nutrition plans must be researched further, especially if the  goal is to maximize dairy farm profits while also maximizing fertility and minimizing disruptions in metabolic profiles.  This review outlines the importance of diet, biochemical profile monitoring, and a dedicated feeding strategy that aids in  developing follicles, ovulation, and conception. By tackling the issues surrounding the transition period, dairy farmers  will be able to increase fertility, decrease postpartum complications, and achieve the goal of “one calf a year programme
Keywords: Cow; Diet; Fertility; Nutrition; Transition period